Fate and deposition of polycyclic aromatic hydrocarbons in the Bransfield Strait, Antarctica. (December 2018) - Cao, Shengkai; Na, Guangshui; Li, Ruijing; Ge, Linke; Gao, Hui; Jin, Shuaichen; Hou, Chao; Gao, Yunze; Zhang, Zhifeng
Abstract: Fifteen polycyclic aromatic hydrocarbons (PAHs) were detected in seawater and atmosphere of Bransfield Strait. The concentration of ∑15 [PAH] in the atmosphere ranged from 3.75 to 8.53 ng m −3, and three-ring PAHs were the most abundant compounds. Dissolved ∑15 [PAH] in seawater ranged from 5.42 to 34.37 ng L −1, and the level of PAHs was markedly different on each side of the strait. The air–sea gas exchange process and molecular diagnostic ratios were calculated, results showed that the environmental behavior of PAHs was net deposition along this cruise. Given the changes in global transport routes of pollutants under global warming, the role of long-range transport (LRT) may be enhanced. Taking the Antarctic as a sink of PAHs due to the LRT and net deposition, PAHs will continue to load into the seawater of this area via atmospheric deposition, which contributes to improving our understanding of the environmental behavior of PAHs. Highlights: Polycyclic aromatic hydrocarbons (PAHs) were investigated in the seawater and atmosphere at Bransfield Strait, Antarctica. Air-water gas exchange exhibited a net deposition trend from atmosphere to Deep Ocean. Antarctic environments still played a sink role of global contaminants. Distribution characteristics of Antarctic contaminants are influenced by both local sources and long-range transport.